Comparison of meat quality characteristics of lambs weaned at eight or 14 weeks of age grazing perennial ryegrass-white clover or a plantain-clover mix - Kok JC; Schreurs NM; Cranston LM; Corner-Thomas RA; Ekanayake WEMLJ; Morris ST; Kenyon PR (New Zealand Society of Animal Production, 2019)
This study compared the meat quality of lambs grazing either perennial ryegrass-white clover pasture or a plantain-clover mix (plantain, red clover, and white clover) from eight to 14 weeks of age followed by a six-week finishing period on perennial ryegrass-white clover pasture. Ewes and their lambs were allocated to four treatments: 1) lambs weaned early (eight weeks of age) on a plantain-clover mix (EARLY), 2) lambs with dam grazing a plantain-clover mix (HERB), 3) lambs with dam grazing pasture >1200 kgDM/ha (HIGH), and 4) lambs with dam grazing pasture <1200 kgDM/ha (LOW). Following the treatment period, all lambs weighing a minimum of 35 kg were sent for slaughter and all remaining lambs were managed and finished as one mob on perennial ryegrass-white clover pasture for a further six weeks. Lambs that reached a minimum 35 kg live weight were slaughtered and meat samples from each lamb were analysed for ultimate pH, meat colour (L*, a*, b*), drip loss and shear force but, no difference was found in objective meat quality characteristics of lambs from different treatments.
Keywords: early wean; lamb; meat quality; plantain-clover mix